(untitled) (African Journal of Biomedical Research, 2021)
Over the years, research on lactic acid bacteria isolated from fish gut against fish gram negative and fish gram positive pathogenic bacteria have been carried out. In this study, lactic acid bacteria of fermented food origin (“wara and fufu”) were examined for their probiotic potentials against fish bacterial pathogens. Samples from fermented cow milk (wara) and fermented cassava (fufu) were stored in ice as: SW6, SW5, SW4, SF4, SF3, and SF2. Serial dilution was carried out with a 10-fold serial dilution. De Man, Rogosa and Sharpe (MRS) agar and de Man, Rogosa and Sharpe (MRS) broth were prepared and used for bacterial growth. Physiological , biochemical charactersations such as gram staining, bile salt tolerance, antibiotics susceptibility test and molecular characterisation of Lactic acid bacteria were carried out. The results revealed that the isolates were gram-positive, catalase negative, cocci, non-haemolytic, and non-pathogenic. The inhibition zones observed were: SW6 (24.7± 0.6) mm against Aeromomas hydrophila, SF4 produced inhibition zone of (16.3±0.6) mm against Aeromomas hydrophila, inhibition zone of (18.5±0.7) mm was produced in SF3 against Bacillus subtilis. All the isolates were susceptible to Chloramphenicol, Ampicillin, Clindamycin and Erythromycin. Molecular characterisation of isolates with high inhibition zones using 16S ribosomal RNA gene partial sequence identified two probiotic strains as SW6 and SF4. These strains were 99% identical to Lactobacillus plantarum strains R762 and AT4. It was deduced from this study that, for the purpose of bio-conservation, probiotics isolated from fermented food origin could replace fish-gut probiotics in treatment of fish bacterial diseases.